Assessing Oral Cancer Awareness Among Dental Students in Van Province, Turkey - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2024)
Objective: The aim of this study was to assess and compare oral cancer awareness among 3rd year and 5th year undergraduate dental students in Faculty of Dentistry, Van Yüzüncü Yıl University. Methods: A validated questionnaire testing oral cancer awareness was distributed to third and fifth year dental students at Faculty of Dentistry, Van Yüzüncü Yıl University. A total of 140 students participated in this survey. Knowledge of oral cancer risk factors and diagnostic procedures, dental students' attitudes towards oral cancers, management practices related to oral cancer and sources of oral cancer information were evaluated using 25 questions. The level of significance was set at p<.05. Results: Among the 140 participating dental students, there were 70 (50.%) third-year and 70 (50%) fifth-year students. The responses of 3rd grade students were significantly lower than 5th grade students in evaluating tobacco use, chewing maras grass and primary oral lesions as risk factors. The rate of 3rd grade students identifying leukoplakia and erythroplakia as the two lesions with the highest susceptibility to carcinogenesis (54.5%) was statistically significantly lower than that of 5th grade students (87.0%). The rate of 3rd grade students (35.9%) identifying squamous cell carcinoma as the most common form of oral cancer was statistically significantly lower than that of 5th grade students (84.1%). Conclusion: This study emphasized the importance of improved training methods for dentistry in oral cancer detection and prevention. As the oral cancer expertise of graduating dental students advances, so does the number of dentists who are informed and competent in delivering proper oral cancer therapy to their patients. In this study, 5th-grade students were shown to be more aware of oral cancer than 3rd-grade students. Keywords Awareness, Dentistry students, Oral cancer, Dental Education
Keywords: Awareness; Dentistry students; Oral cancer; Dental Education